Emblem Project Utrecht : Dutch Love Emblems of the Seventeenth Century - Universiteit Utrecht (2007)
[Dt.:] Das Forschungsprojekt digitalisiert und analysiert niederländische Liebes-Embleme der Renaissance. Bislang sind 10 Emblembücher als Volltexte zu blättern. Die Embleme werden ikonographisch analysiert, die Texte sind transkribiert. - [Engl.:] Project aim is the digitisation of Dutch love emblems. At this moment, ten books have been digitised. For these there are full transcription, page facsimiles and some indexes.